2016
DOI: 10.1177/0891988716673468
|View full text |Cite
|
Sign up to set email alerts
|

Problem Gambling in a Sample of Older Adult Casino Gamblers

Abstract: As older adults continue to make up a greater proportion of the Canadian population, it becomes more important to understand the implications that their leisure activities have for their physical and mental health. Gambling, in particular, is a form of leisure that is becoming more widely available and has important implications for the mental health and financial well-being of older adults. This study examines a large sample (2103) of casino-going Ontarian adults over the age of 55 and identifies those featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Since the population of Canada is aging and the Baby Boom cohort remains sizable compared to other age groups (Bohnert et al 2015), it is likely that the number of people who gamble will increase, including those at low and moderate risk levels. In this context, it is also worth examining outcomes experienced by older adults who participate in recreational gambling to better understanding protective factors that contribute to quality of life (Tse et al 2012). This group has been largely overlooked in previous research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the population of Canada is aging and the Baby Boom cohort remains sizable compared to other age groups (Bohnert et al 2015), it is likely that the number of people who gamble will increase, including those at low and moderate risk levels. In this context, it is also worth examining outcomes experienced by older adults who participate in recreational gambling to better understanding protective factors that contribute to quality of life (Tse et al 2012). This group has been largely overlooked in previous research.…”
Section: Discussionmentioning
confidence: 99%
“…Older adults may be especially vulnerable to problem gambling due to age-related stressors, such as feelings of isolation due to the death of a spouse and/or close friends, chronic health conditions that make it difficult to participate in other activities, boredom, and reliance on a fixed income (Ashe et al 2008;Southwell et al 2008). Older adult problem gamblers age 60 and over are more likely to experience social problems, physical health problems, and psychological difficulties than non-problem gamblers (Ariyabuddhiphongs 2012;Erickson et al 2005;Pietrzak and Petry 2006;Tse et al 2012). Others have noted that social isolation may make older adults vulnerable to higher levels of participation (Subramaniam et al 2015;Tse et al 2012).…”
Section: Benefits and Harmsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been widely observed that older adult populations have lower prevalence rates of disordered gambling than their younger counterparts ( Subramanian et al., 2015 ). However, older adults with a gambling disorder often experience higher levels of psychological and physical comorbidity compared with younger adults ( Chou & Afifi, 2011 ; Hong, Sacco, & Cunningham-Williams, 2009 ; Van der Maas et al., 2017 ). In particular, anxiety and depression result in more complex treatment requirements for this population in contrast to younger treatment-seeking adults ( Kerber, Black, & Buckwalter, 2008 ).…”
Section: Introductionmentioning
confidence: 99%